Optimum web viewer application for DICOM whole slide image visualization in anatomical pathology. (October 2019) - Lajara, Nieves; Espinosa-Aranda, Jose Luis; Deniz, Oscar; Bueno, Gloria
Highlights: Performance of Visilab Viewer achieved the topmost qualitative and quantitative results in comparison with other visualization web systems. The proposed DICOM-based architecture was successfully used in real industrial environments with different manufacturers of digital pathology scanners. Interoperability in digital pathology still needs to be verified with real connectivity tests. Web systems based on DICOM as Visilab Viewer allows telepathology and proper collaborative work during diagnosis. Abstract: Background and Objective: Digital scanners are being increasingly adopt-ed in anatomical pathology, but there is still a lack of a standardized whole slide image (WSI) format. This translates into the need for interoperability and knowledge representation for shareable and computable clinical information. This work describes a robust solution, called Visilab Viewer, able to interact and work with any WSI based on the DICOM standard. Methods: Visilab Viewer is a web platform developed and integrated alongside a proposed web architecture following the DICOM definition. To prepare the information of the pyramid structure proposed in DICOM, a specific module was defined. The same structure is used by a second module that aggregates on the cache browser the adjacent tiles or frames of the current user's viewport with the aim of achieving fast and fluid navigation over the tissue slide. This solution was tested and compared with three different web viewers, publicly available, with 10 WSIs. Results: A quantitative assessment was performed based on the average load time per frame together with the number of fully loaded frames. Kruskal–Wallis and Dunn tests were used to compare each web viewer latency results and finally to rank them. Additionally, a qualitative evaluation was done by 6 pathologists based on speed and quality for zooming, panning and usability. The proposed viewer obtained the best performance in both assessments. The entire architecture proposed was tested in the 2nd worldwide DICOM Connectathon, obtaining successful results with all participant scanner vendors. Conclusions: The online tool allows users to navigate and obtain a correct visualization of the samples avoiding any restriction of format and localization. The two strategical modules allow to reduce time in displaying the slide and therefore, offer high fluidity and usability. The web platform manages not only the visualization with the developed web viewer but also includes the insertion, manipulation and generation of new DICOM elements. Visilab Viewer can successfully exchange DICOM data. Connectathons are the ultimate interoperability tests and are therefore required to guarantee that solutions as Visilab Viewer and its architecture can successfully exchange data following the DICOM standard. Accompanying demo video. (Link to Youtube video.)